The ROLE OF OBESITY IN BREAST CANCER METASTASIS - Fadila Gustiani Daraz; Indri Windarti; Putu Ristyaning Ayu Sangging (Medula, 2023)
Breast cancer is the most common type of cancer in women worldwide. One of the factors that are believed to have a role in the development and growth of breast cancer is nutritional status which can be associated with the body mass index of adult patients. It is estimated that overweight and obesity are risk factors for the spread of breast cancer to distant metastases. Mechanism of spread through two ways, estrogen and leptin. Aromatase is an enzyme in estrogen biosynthesis that promotes tumor growth through its expression in breast adipose stromal cells. Meanwhile, leptin is produced by adipocytes. Adipocytes that experience hypertrophy and hyperplasia cause pathophysiological changes that affect the development of breast cancer. Various case studies show that a diet high in fat and calories is associated with breast cancer. The high risk of obesity for breast cancer metastases. This is important to be studied further because of the large number of cases of breast cancer both globally, in Indonesia and in Lampung. This review article is important to know the relationship between obesity and breast cancer metastases, as scientific information and knowledge, and can be used as material for dietary intervention in obese breast cancer patients.